2008
DOI: 10.1111/j.1439-0396.2007.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effect of α‐ketoglutarate, given early in postnatal life, on both growth and various bone parameters in pigs

Abstract: The long-term effect of alpha-ketoglutarate (AKG) given for 21-24 days post-partum, on the skeleton of commercial pigs, was investigated. In experiment A, 12 pigs were given AKG [0.1 g/kg of body weight (b.w.) per day per os], while 12 controls were administered vehicle. At day 169, the left and right femur, humerus and sixth ribs were analysed for mechanical and geometrical properties and quantitative computed tomography. In experiment B, 32 piglets were divided equally into an AKG group (0.3 g/kg of b.w. per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…Alpha-ketoglutarate is formed during the Krebs cycle and can also be synthesized by certain anaerobic bacteria, including several species of Bacteriodes (Allison et al 1979). Increased levels have been associated with a number of benefits including: increased bone growth as measured by the length of the 6th rib in pigs (Andersen et al 2008), decreased cholesterol levels in rats (Radzki et al 2009), protection of gut mucosa and kidney function (Dabek et al 2005), and possible prevention of inappropriate muscle catabolism during times of stress, such as surgery, injury and illness (Wiren et al 2002). As with several other observed metabolite differences, the increase in alpha ketoglutarate is likely due to changes in the composition of the intestinal microbe population.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-ketoglutarate is formed during the Krebs cycle and can also be synthesized by certain anaerobic bacteria, including several species of Bacteriodes (Allison et al 1979). Increased levels have been associated with a number of benefits including: increased bone growth as measured by the length of the 6th rib in pigs (Andersen et al 2008), decreased cholesterol levels in rats (Radzki et al 2009), protection of gut mucosa and kidney function (Dabek et al 2005), and possible prevention of inappropriate muscle catabolism during times of stress, such as surgery, injury and illness (Wiren et al 2002). As with several other observed metabolite differences, the increase in alpha ketoglutarate is likely due to changes in the composition of the intestinal microbe population.…”
Section: Discussionmentioning
confidence: 99%
“…Early treatment with α‐ketoglutarate at a daily dosage of 0.1 g (kg body weight) −1 induced positive long‐term effects on the skeletal system and increased vBMD and the mechanical strength of femur and ribs (Harrison et al 2004; Tatara et al 2007 c ). In newborn pigs, 3 weeks of neonatal administration with AKG improved bone strength, and this effect was associated with an elevated plasma concentration of 17β‐oestradiol (Andersen et al 2008). Similarly to the increase of serum concentration of GH and IGF‐1 in 21‐day‐old lambs in the present study, AKG elevated plasma 17β‐oestradiol levels in pigs only during the period of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal administration of HMB had long‐term effects on bone tissue owing to improved somatotrophic axis function and increased volumetric bone mineral density, as well as geometrical and mechanical properties of the femur in the offspring (Tatara et al 2007 b ). In other studies on pigs, 3 weeks of neonatal administration of α‐ketoglutarate (AKG) induced positive long‐term effects on skeletal system properties that were investigated at the slaughter age (Andersen et al 2008). Similar results were obtained in sheep given AKG during the first 2 weeks of life.…”
mentioning
confidence: 99%
“…We demonstrated that the LP + 1.0%A and LP + 1.5%A groups show greater mRNA levels for CAT1, EAAC1 increasing the growth performance of piglets. AKG has been reported to promote protein synthesis by increasing the phosphorylation of the mTOR complex, S6K1 and 4E-BP1 (Andersen, Tatara, Krupski, Majcher, & Harrison, 2008;Chen et al, 2018).…”
Section: Consequently Akg Promotes N Depositions In Cells Throughoutmentioning
confidence: 99%
“…AKG has been reported to promote protein synthesis by increasing the phosphorylation of the mTOR complex, S6K1 and 4E-BP1(Andersen, Tatara, Krupski, Majcher, & Harrison, 2008;Chen et al, 2018).Recently, it has been reported that LP diet supplementationwith AKG can increase the phosphorylation of both downstream effectors of the mTOR signalling pathway in skeletal muscle of piglets, moreover, inhibiting proteolysis via the Akt/mTOR pathway(Cai et al, 2016). AKG is a crucial intermediate in the TCA cycle and can be used to produce ATP and amino acids in animal tissues and intestine.…”
mentioning
confidence: 99%